Pengolahan Sampah yang Inovatif untuk Meningkatkan Ekonomi dan Kesejahteraan Keluarga - Fitri Suryani; Anizar Rahayu; Nur Idaman; Sri Sintawati; Andika Yunianto (IKRA-ITH ABDIMAS, 2023)
The purpose of this community service activity is to provide assistance for PartnersCommunities in Pringkasap Village, Pabuaran District, Subang Regency – West JavaIndonesia in increasing awareness about environmental sustainability and cleanliness, aswell as improving skills in managing waste. This mentoring activity is carried out in orderto answer the problems faced by partners about 1) Lack of awareness of residents inmaintaining environmental sustainability and cleanliness, 2) Lack of knowledge aboutsorting waste from the source, and 3) How to use waste for economic value. Theimplementation of mentoring consists of stages: 1) interviews and partner observations, 2)socialization. and 3) Counseling on how to increase citizen awareness in maintainingenvironmental sustainability and cleanliness, Providing knowledge about waste sortingand how to use waste for economic value.